2012
DOI: 10.1038/ncomms2019
|View full text |Cite
|
Sign up to set email alerts
|

Charge stripe order near the surface of 12-percent doped La2−xSrxCuO4

Abstract: A collective order of spin and charge degrees of freedom into stripes has been predicted to be a possible ground state of hole-doped Cuo 2 planes, which are the building blocks of hightemperature superconductors. In fact, stripe-like spin and charge order has been observed in various layered cuprate systems. For the prototypical high-temperature superconductor La 2 − x sr x Cuo 4 , no charge-stripe signal has been found so far, but several indications for a proximity to their formation. Here we report the obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 39 publications
6
50
2
Order By: Relevance
“…Recent experiments in cuprates have revealed ample evidence for incommensurate charge modulations with wavevectors oriented along the crystalline axes, i.e., at 45˝off the SDW vector as well [8,[44][45][46][47][48][49][50][51][52][53][54]. A theoretical investigation examining a multiorbital model of cuprates finds support for such an axial charge order [46] in contrast to previous calculations, which reported wave vectors along the Brillouin zone diagonal.…”
Section: Charge Order In Cuprates and Other Unconventional Superconducontrasting
confidence: 43%
“…Recent experiments in cuprates have revealed ample evidence for incommensurate charge modulations with wavevectors oriented along the crystalline axes, i.e., at 45˝off the SDW vector as well [8,[44][45][46][47][48][49][50][51][52][53][54]. A theoretical investigation examining a multiorbital model of cuprates finds support for such an axial charge order [46] in contrast to previous calculations, which reported wave vectors along the Brillouin zone diagonal.…”
Section: Charge Order In Cuprates and Other Unconventional Superconducontrasting
confidence: 43%
“…The CDW order in YBa 2 Cu 3 O 6+d appears at temperatures as high as ∼ 150 K in a lattice with OI order present to above room temperature. Finally, we note that charge-stripe order has recently been detected by x-ray diffraction in La 2−x Sr x CuO 4 with x ∼ 0.12 [73][74][75][76], confirming an earlier identification by nuclear magnetic resonance [77]. This result is somewhat surprising, as the average structure of La 2−x Sr x CuO 4 is LTO (although electron diffraction studies have indicated LTT-like regions at LTO twin boundaries for x = 0.12 [78] and LTLO order for x = 0.115 [79]).…”
Section: Discussionmentioning
confidence: 99%
“…There have been three recent reports [26][27][28] of x-ray studies of the CDW in La 1.88 Sr 0.12 CuO 4 , one of the compositions studied here, in the last two years. These studies used resonant and non-resonant diffraction techniques with x-ray energies from 529 eV to 100 keV.…”
Section: Introductionmentioning
confidence: 99%